23. Scientific Statistical Seminar “Wrocław-Marburg” - Marciniuk, Agnieszka (Silesian Statistical Reviev, 2016)
This year’s 23. Scientific Statistical Seminar “Wrocław-Marburg” was held between 28.09 and 1.10.2015 in the village of Pottenstein near Nuremberg.
Śląski Przegląd Statystyczny = Silesian Statistical Review, 2016, Nr 14 (20), s. 203-205